2014
DOI: 10.1179/1743281214y.0000000194
|View full text |Cite
|
Sign up to set email alerts
|

Application of biomass fuel in iron ore sintering: influencing mechanism and emission reduction

Abstract: The influence of biomass fuel replacing coke breeze on flame front and combustion efficiency were studied. The results show that when coke breeze is replaced, the flame front is accelerated since biomass has superior combustion characteristics. Combustion efficiency is decreased, however, as biomass is of excessively high reactivity, which can both lower the maximum temperature and reduce the time at high temperature of the sinter bed. The proportion of biomass fuel replacing coke breeze should, therefore, not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…The main fuel used in sintering process is the undersize coke or coke breeze which is generated during coke screening. Sintering contributes to the total iron and steel industry CO 2 emission by approximately 10% [52]. The CO 2 in this case is a result of combustion of coke breeze and the calcination of limestone for example.…”
Section: Sinteringmentioning
confidence: 99%
See 1 more Smart Citation
“…The main fuel used in sintering process is the undersize coke or coke breeze which is generated during coke screening. Sintering contributes to the total iron and steel industry CO 2 emission by approximately 10% [52]. The CO 2 in this case is a result of combustion of coke breeze and the calcination of limestone for example.…”
Section: Sinteringmentioning
confidence: 99%
“…Such decrease in post combustion results in lowering the combustion zone temperature by 150 • C (from~1390 • C in case of coke breeze to~1240 • C in case of bio-char). Other researchers have demonstrated that up to 40% bio-char can replace coke breeze without negatively affecting the process [52]. The replacement ratio can be further increased through utilization of composites of coke and bio-char [50].…”
Section: Sinteringmentioning
confidence: 99%
“…These methods to control NOx contain selective catalytic reduction, 17) selective non-catalytic reduction, 18) flue gas recirculation, 19) process parameter control, 20,21) modification of fuel, 22) as well as biomass utilization, etc. 23,24) Flue gas recirculation sintering is a potential method to reduce NOx emissions. It has many advantages including decreasing fuel consumption and pollutant emissions, etc.…”
Section: Effects Of Temperature and Circulating Flue Gas Components On Combustion And No X Emissions Characteristics Of Four Types Quasi-mentioning
confidence: 99%
“…Moreover, SO 2 and NOx emissions during sintering account for 60% and 50% of the overall emissions of SO 2 and NOx in steel production, respectively [1]. At present, new technologies for reducing NOx emission during sintering mainly include flue gas recirculation sintering (FGRS), selective catalytic reduction [2], biomass fuel [3][4][5][6], gas injection [7], and parameter control [8,9].…”
Section: Introductionmentioning
confidence: 99%